ETHICAL AND LEGAL ASPECTS OF ANIMAL CLONING: AN ANALYSIS IN THE LIGHT OF THE FILM JURASSIC WORLD Â€“ DOMAIN - Sobreira, Patràcia; Rammàª, Rogà©rio; Franà§a, Paulo Henrique (CIPEEX, 2022)
THE MAIN THEME OF THIS ARTICLE IS ANIMAL CLONING AND ITS ETHICAL AND LEGAL IMPLICATIONS FROM THE ANALYSIS OF THE MOVIE €ŒJURASSIC WORLD - DOMINION€. AT THE SAME TIME, IT SEEKS TO POINT OUT HOW GENETIC MANIPULATION AFFECTS HUMANITY, RAISING A BROAD DEBATE ABOUT VALUE JUDGMENT. THE INVESTIGATION WAS CONSTITUTED AT DIFFERENT TIMES: INITIALLY IT SOUGHT TO UNDERSTAND THE NORMATIVE FRAMEWORK OF ANIMAL EXPERIMENTATION IN BRAZIL, LAW Nº 11.794/08 - AROUCA LAW - SUBSIDIZING THE CONSTRUCTION OF THE THEORETICAL FRAMEWORK ON THE INDICATORS USED IN THE RESEARCH, WITH EMPHASIS ON ALTERNATIVE METHODS ; IN A SECOND MOMENT, ANIMAL CLONING WAS VERIFIED AND, IN PARTICULAR, THE BILL 5010/13, INITIATED BY SENATOR KTIA ABREU, WHICH DEALS WITH THE CONTROL OF ANIMAL GENETIC MATERIAL AND THE OBTAINING AND SUPPLY OF CLONES OF DOMESTIC ANIMALS. INTENDED FOR THE PRODUCTION OF DOMESTIC ANIMALS OF ZOOTECHNICAL INTEREST AND WHICH WAS APPROVED IN DECEMBER 2021 BY THE COMMITTEE ON THE ENVIRONMENT AND SUSTAINABLE DEVELOPMENT OF THE CHAMBER OF DEPUTIES. ALSO, THE MOVIE €ŒJURASSIC WORLD - DOMINION€ WAS ANALYZED, RELEASED IN BRAZIL ON JUNE 2ND THIS YEAR, WHICH ALSO MAKES REFERENCE TO THE CLONING OF HUMAN AND NON-HUMAN ANIMALS.&NBSP; AFTERWARDS, AN ANALYSIS OF THE RESEARCH WAS CARRIED OUT WITH THE FIRST CLASS OF THE POST-GRADUATE COURSE IN ANIMAL LAW AND JUS-ANIMAL PRACTICE OF THE IESF (INSTITUTO DE ENSINO SUPERIOR DE FORTALEZA) THROUGH QUESTIONNAIRES, WHERE THE CONCERN OF THE STUDENTS TO THE ETHICAL DILEMMAS ABOUT SCIENTIFIC RESEARCH ON ANIMAL CLONING. FINALLY, WHAT IS PROPOSED THROUGH THE RESULTS IS THE TRIANGULATION OF DATA AIMING AT A BETTER UNDERSTANDING OF ITS OBJECTIVES. A LITERATURE REVIEW BASED ON SCIENTIFIC WORKS CONTAINED IN THE ELECTRONIC DATABASES: GOOGLE SCHOLAR AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) IS PRESENTED. THE THEORETICAL FRAMEWORK WAS BASED ON THE CONCEPTS OF ANIMAL EXPERIMENTATION, CLONING, BIOETHICS, ANIMAL DIGNITY, RELYING ON DIFFERENT THEORETICAL CONTRIBUTIONS AND DIALOGUING WITH DIFFERENT AUTHORS. IN THIS CONTEXT, THE METHODOLOGY WAS A RESEARCH WITH A QUALITATIVE-QUANTITATIVE APPROACH, BASED ON THE HERMENEUTIC METHOD, DATA COLLECTION THROUGH QUESTIONNAIRES THROUGH GOOGLE FORMS, AND CONTENT ANALYSIS TECHNIQUE. DIAGNOSTIC STUDIES LIKE THIS ARE IMPORTANT TO VISUALIZE THE CURRENT SCENARIOS OF ANIMAL CLONING. IN POSSESSION OF THE CONCEPTS OBTAINED AND BASED ON THE COLLECTED MATERIALS, IT IS INTENDED TO CONCLUDE THAT THERE ARE SEVERAL ETHICAL POSITIONS ON THE MATTER. HOWEVER, WITHIN THE FRAMEWORK OF THESE VARIETIES OF UNDERSTANDINGS ABOUT HUMAN CONDUCT, SUCH POSITIONS CAN COEXIST HARMONIOUSLY WITHIN THE FRAMEWORK OF A LARGER PARADIGM, WHERE SCIENTIFIC THINKING AND TECHNICAL ACTION ARE SUBSUMED UNDER A CERTAIN DEMOCRATICALLY INSTITUTED ETHICAL FRAMEWORK, BASED ON RESPECT FOR LIFE AND ANIMAL DIGNITY. &NBSP;&NBSP;